Development of Student Worksheets Using the Context of Local Wisdom on Integers and Fractions - Deda, Yohanis Ndapa; Maifa, Talisadika (Mathematics Education Journal, 2021)
The purpose of this research is to develop a valid, practical and effective junior high school mathematics worksheet. Local wisdom referred to in this study is a traditional food, namely Jagung Bose, Jagung Katemak, Ut Kono, and Laku Tobe, which have become a daily diet for the people of the Indonesia-Timor Leste border community on the Pulau Timor. This research is a kind of development research using the Tessmer formative evaluation model, which consists of two stages of development, namely the preliminary analysis stage and the formative evaluation stage. The subject of this research is the 9th-grade students of Taloeb Junior High School in the border area in 2020. The data collection techniques used include tests, learning outcomes, observation, and interviews. Experts have validated the development of student worksheets using the context of local traditional food wisdom with the results of assessments from material experts, media experts and linguists. Validated by Experts, Students Worksheets (SW) of maths included in the very good category and trial results have shown that the SW meets the practical criteria and has a potential effect on improving junior high school students' mathematics skills and learning outcomes. DOI: https://doi.org/10.22342/jpm.v.i.12824.71-82